Playing social justice: How do early childhood teachers enact the right to play through resistance and subversion? - Albin-Clark, Jo; Archer, Nathan (PRISM: Casting New Light on Learning, Theory and Practice, 2023)
In this paper we narrate how two teachers enact playful pedagogies by resisting the single story of formalised learning discourses in early childhood education and care. Playful learning is well established in international literature and children have the right to play. Yet in contemporary outcomes-driven policy, adult-led formalised teaching has become normalised at the expense of child-initiated play. Play is thus marginalised; positioned as a privilege rather than as a right and dependent on views of children as capable holders of rights. Here, we position play in relation to democracy, equity and social justice by storying how teachers’ circumvent scrutiny to facilitate the right to play and we argue this as a fruitful sub-context for resistance. From this perspective, teachers’ resistances do not just enable play, they embody and enact representative and democratic justice. Firstly, teachers story representative forms of social justice as ‘being the right thing’ in making play happen. Secondly, teachers enact democratic forms of social justice through resistance actions of ‘doing the right thing’ that entangle an emotional vulnerability to scrutiny. Adopting alternative resistance positions shifts play beyond a privilege and creates transformational spaces for social justice where time, space and materiality have a role to play. We call on teachers and educators to deepen their critical awareness of the narrowness of a single story of learning and the rich relationships between rights and play agendas. We assert that teachers’ resistances can enable playful pedagogies and act as hopeful storytelling of social justice as serious play.